1972
DOI: 10.1002/ar.1091730107
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage canals, their morphology and distribution

Abstract: The proximal humeral chondroepiphysis of newborn pups was shown to be well-vascularized by a series of segmentally distributed cartilage canals which varied from short unbranched channels to channels which coursed half-way across the epiphysis. Cartilage canals were observed to contain a muscular arteriole, venule, loose connective tissue and perivascular capillaries. The muscular arterioles originated from the dense perichondrial vascular network at regular intervals, coursed in the central portion of the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
5

Year Published

1978
1978
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 15 publications
6
75
0
5
Order By: Relevance
“…132 When early lesions were studied by micro-CT with sufficient resolution to detect trabecular bone micro-fractures, the results indicated that micro-fracture was not the cause of the studied lesions (Table 3). 77 There is evidence to support, and little reason to doubt, that physiological 28,117 or traumatic 71 47,70 Cartilage canals were studied and retained cartilage a was found at predilection sites in the shoulder and stifle joints of 3-day-old to 9-month-old puppies 123 Chondrocyte necrosis was found in the medial coronoid process in 5-to 12-week-old predisposed puppies 59 Vascular response indicates that cartilage canal vessels were transected when different types of defects were created in the medial and lateral femoral condyles of puppies 11 Perfusion of the proximal humerus was studied in 1-to 7-day-old English Pointer and mongrel puppies 124,125 Blood supply to the medial coronoid process was studied by serial histological sectioning in 4-to 24-weekold Golden Retriever puppies 126 Humans Adult-and juvenile-onset osteochondritis dissecans are recognized. The form that is most similar to osteochondrosis dissecans in animals is the juvenile form.…”
Section: Causes Of Vascular Failurementioning
confidence: 99%
“…132 When early lesions were studied by micro-CT with sufficient resolution to detect trabecular bone micro-fractures, the results indicated that micro-fracture was not the cause of the studied lesions (Table 3). 77 There is evidence to support, and little reason to doubt, that physiological 28,117 or traumatic 71 47,70 Cartilage canals were studied and retained cartilage a was found at predilection sites in the shoulder and stifle joints of 3-day-old to 9-month-old puppies 123 Chondrocyte necrosis was found in the medial coronoid process in 5-to 12-week-old predisposed puppies 59 Vascular response indicates that cartilage canal vessels were transected when different types of defects were created in the medial and lateral femoral condyles of puppies 11 Perfusion of the proximal humerus was studied in 1-to 7-day-old English Pointer and mongrel puppies 124,125 Blood supply to the medial coronoid process was studied by serial histological sectioning in 4-to 24-weekold Golden Retriever puppies 126 Humans Adult-and juvenile-onset osteochondritis dissecans are recognized. The form that is most similar to osteochondrosis dissecans in animals is the juvenile form.…”
Section: Causes Of Vascular Failurementioning
confidence: 99%
“…125 However, canals from the cartilage may cross into the underlying bone, where they form anastomoses with vessels in the bone marrow. 46,136 The functions of the cartilage canals are not fully understood, but they are suggested to serve three purposes: 1) to nourish chondrocytes beyond the reach of diffusive nutrients from the synovial fluid, 46,127,132 2) to play a role in the formation and maintenance of the secondary ossification center, 124,132 and 3) to supply both cartilage and bone with mesenchymal stem cells. 42,64,126 As the individual grows, the growth rate of the cartilage diminishes compared with the rate of progression of the ossification front, causing the ossification front to advance toward the articular cartilage and resulting in the layer of growth cartilage becoming progressively thinner (Fig.…”
Section: Enchondral Ossificationmentioning
confidence: 99%
“…A long debate surrounds the role cartilage canals in vertebrates; however, it is generally accepted that they are necessary for nourishment of the growing chondroepiphysis (Wilsman and Van Sickle, 1972). In addition, it has repeatedly been considered that these canals supply long bones (Lutfi, 1970;Kugler et al, 1979;Burkus et al, 1993;Ganey et al, 1995;Rivas and Shapiro, 2002;Á lvarez et al, 2005a,b) as well as short bones (Fritsch et al, 2001) with osteogenic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these observations, cartilage canals are considered essential for endochondral bone development in the avian epiphysis (Blumer et al, 2005(Blumer et al, , 2006. Interestingly, it was noted that in several mammals cartilage canals can regress as the animal gets older (Wilsman and Van Sickle, 1972;Cole and Wezeman, 1985;Ytrehus et al, 2004a,b). This event is a physiological age-dependent process described as chondrification in which the vessels degenerate and the mesenchymal cells are converted into matrix-producing chondrocytes, occluding the lumen of the canal.…”
Section: Introductionmentioning
confidence: 99%